Sosialisasi Anti Hoax Di SMPN Islam 2 Kota Ternate - Mustamin Hamid; Alfanugrah A. Hi Usman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hoax news is fake news that is made up or distorted from actual reality. There are many cases or events that did not actually happen but are made into news and packaged as well as possible so that the public is interested in reading them. As a modern and educated society, we have to be good at digging up information. This Community Service activity was carried out at SMPN 2 Islam Ternate City where this activity aims to open the minds of students at SMPN 2 Islam Ternate City regarding the importance of filtering information so that they do not become a generation that likes to spread untrue news. With this activity, it is hoped that students will become more active in finding out about news circulating in the community and school environment, finding out whether the news is true or not before it is distributed widely so as to minimize the spread of hoax news.